Response of Different Varieties to Irrigation Intervals on Growth and Dry Seeds Yield of Broad Bean (Vicia Faba L) - Ali Al-Assaf , Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
The experiment was conducted in a vegetable research field at Technical Agricultural College, Mosul. It was intended to investigate the effects of two factors, namely, three irrigation intervals (4, 8, and 12 days) and four varieties (Local, Syrian, Turkish, and French). The effect of these factors was examined in relation to plant growth and total dry seed yield of broad beans in northern Iraq, specifically Nineveh Governorate. The study results showed that the first treatment with an irrigation interval of 4 days as a supplement considerably improved all characters of growth, including plant height and branch number, as well as dry seed yield components represented by the number of pods/plants, the number of seeds/pods, pod length, and seed yield/plant. Hence, the total dry seed yield was 7.235 tons/hectare. The French variety demonstrated a significant increase represented by 8.276 tons/hec in terms of all characters as compared to other varieties, namely, local, Syrian, and Turkish.